2017
DOI: 10.1177/0886260517700618
|View full text |Cite
|
Sign up to set email alerts
|

Examining the Relationship Between Intimate Partner Violence and Concern for Animal Care and Safekeeping

Abstract: The current study examined the knowledge and experience of animal welfare and human service providers in urban and rural communities of Saskatchewan, Canada. Nine exploratory qualitative interviews were conducted to gather a more in-depth understanding of whether the concern for animal care and safekeeping impacts the decision to leave situations of intimate partner violence. The interviews were semistructured and guided by four questions, which were designed, reviewed, and revised based on feedback from a com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
35
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(37 citation statements)
references
References 16 publications
2
35
0
Order By: Relevance
“…Given transportation barriers, it can be difficult to take pets when escaping and finding safekeeping or fostering options for pets can prove challenging in small communities. Further, for women who work on farms and own livestock, leaving an abusive relationship means giving up their livelihood, and leaving animals behind-potentially risking the animals' well being (Wuerch et al 2018;Wuerch et al 2017). For these reasons, women who own animals may delay leaving or stay in a home where IPV is taking place.…”
Section: Geographic Barriers By Distancementioning
confidence: 99%
“…Given transportation barriers, it can be difficult to take pets when escaping and finding safekeeping or fostering options for pets can prove challenging in small communities. Further, for women who work on farms and own livestock, leaving an abusive relationship means giving up their livelihood, and leaving animals behind-potentially risking the animals' well being (Wuerch et al 2018;Wuerch et al 2017). For these reasons, women who own animals may delay leaving or stay in a home where IPV is taking place.…”
Section: Geographic Barriers By Distancementioning
confidence: 99%
“…This is in line with the findings in the study by Wuerch and colleagues (2017), where all staff members reported being aware of women who refused to go to a shelter because their pet was not allowed to accompany them. A limitation of most of the research on the co-occurrence of animal abuse and IPV (with Wuerch et al, 2017, as a recent exception) is the reliance on samples of women who are already in shelters; it is therefore unknown how many women may never leave an abusive partner due to concern for their pet. Although we do not yet have an estimate of the proportion of people in the community who remain in abusive relationships due to concern for their pets, the fact that such large proportions of staff members in these studies are aware of women who need support for both themselves and their companion animals provides further evidence of the need to establish pet safekeeping programs.…”
Section: Discussionmentioning
confidence: 99%
“…Ad hoc solutions (e.g., pooling resources to access a local kennel, contacting a local animal care agency, or a staff member fostering the animal) were the norm and represented creative solutions to ensure the woman's and the animal's safety. More recently, Wuerch, Giesbrecht, Price, Knutson, and Wach (2017) explored challenges surrounding the provision of services to women with pets, including obstacles to pet safekeeping and agency needs to provide services. In interviews with nine domestic violence service providers and animal welfare agency staff in Saskatchewan, Canada, all respondents noted that they knew of women who had refused to go to a shelter because they could not bring their pets.…”
Section: Survivors' Relationships With Pets In the Context Of Ipvmentioning
confidence: 99%
See 1 more Smart Citation
“…Indeed, concern for the wellbeing of any animals left behind is acknowledged by some service providers as a significant barrier to leaving violent situations (e.g., Wuerch, Giesbrecht, Price, Knutson & Wach, 2017), with increasing focus on the need to provide refuge for all victims of DVA (e.g., Collins et al 2017). In part, this acknowledgment comes from a recognition of the strong bonds between (some) humans and their animal companions.…”
Section: Literature Review 'The Link' Between Animal Abuse and Dvamentioning
confidence: 99%